Analysis of crack growth problems using the object-oriented program bemcracker2D - Gilberto Gomes; Antonio C O Miranda (Fracture and Structural Integrity, 2018)
This paper presents an application of the boundary element method to the analysis of crack growth problems in linear elastic fracture mechanics and the correlation of results with experimental data. The methodology consists of computing stress intensity factors (SIFs), the crack growth path and the estimation of fatigue life, via an incremental analysis of the crack extension, considering two independent boundary integral equations, the displacement and traction integral equations. Moreover, a special purpose educational program for simulating two-dimensional crack growth based on the dual boundary element method (DBEM), named BemCracker2D, written in C++ with a MATLAB graphic user interface, has been developed and used to verify the adopted methodology. The numerical results are compared with those of the finite element method (FEM) and correlated with experimental data of fatigue crack-growth tests for two-dimensional structural components under simple loading, aiming to demonstrate the accuracy and efficiency of the methodology adopted, as well as to evaluate the robustness of the BemCracker2D code.